Avaliação comparativa do potencial osteocondutor de quatro diferentes substitutos ósseos em defeitos críticos em calvárias de coelhos - Grossi-Oliveira, Gustavo Augusto [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Objectives: To evaluate the osteoconductive potential of four biomaterials used in bone defects filling in rabbit’s calvaria. Methods: 24 male Albinus rabbits underwent to bone defect creation of 8 mm in diameter bilaterally in calvaria region. The groups were divided acordind to the bone substitute used to fill the calvaria defect: bovine hydroxyapatite - Bio-Oss ® (BIO), Lumina Bone Porus® (LBP) and Bonefill® (BFL), and an alloplastic material - Clonos® (CLN), and were submitted to euthanasia at 14 and 40 days after the surgery. The removed pieces were processed, histological slides were obtained and subjected to histological analysis; histometric analysis, through the measurement of newly formed bone area (NB) in the center of the defects; immunohistochemical analysis, by labelling the Runt-related transcription factor 2 (Runx2), vascular endothelial growth factor (VEGF) and osteocalcin (OC). Quantitative data were statistically analyzed (α = 0.05). Results: The CLN group showed greater AON in both periods analyzed in relation to the other groups (p <0.001, Tukey test). At 14 days, the AON showed greater values in BIO in relation with LBP and BFL groups, however , after 40 days, the LBP group surpassed the results of BIO (p <0.001, Tukey test). The immunostaining showed a decrease in Runx2 intensity in BIO after 40 days, while it increased for LBP (p <0.05, Tukey test). The CLN showed increased OC compared to the other groups in both periods analyzed (p <0.05, Tukey test). Conclusions: The CLN showed the best osteoconductive behavior in critical defects in rabbit’s calvaria.

Objetivos: Avaliar o potencial osteocondutor de quatro biomateriais utilizados no preenchimento de defeitos ósseos críticos em calvárias de coelhos. Material e métodos: 24 coelhos machos albinus foram submetidos à confecção de defeito ósseo de 8 mm de diâmetro na calvária bilateralmente. Os grupos foram divididos aleatoriamente pelos materiais utilizados: hidroxiapatita bovina - Bio-oss®(BIO), Lumina Bone Porus®(LBP) e Bonefill®(BFL) e, um material aloplástico - Clonos® (CLN), submetidos à eutanásia aos 14 e 40 dias após a cirurgia. A descalcificação das peças foi realizada e assim, as lâminas obtidas foram submetidas às análises histológica; análise histométrica, por meio da mensuração da área de osso neoformado (AON) no centro dos defeitos; análise imunoistoquímica, por meio da marcação do fator 2 de transcrição relacionado a Runt (Runx2), fator de crescimento do endotélio vascular (VEGF) e osteocalcina (OC). Os dados quantitativos foram submetidos à análise estatística (=0,05). Resultados: O grupo CLN mostrou maior AON nos dois períodos analisados em relação aos demais grupos (p<0,001, Teste Tukey). Aos 14 dias, o BIO foi superior quanto a AON aos grupos LBP e BFL, entretanto aos 40 dias, o grupo LBP superou os resultados do BIO (p<0,001, Teste Tukey). A imunomarcação para Runx2 mostrou diminuição na intensidade para BIO aos 40 dias, enquanto que aumentou para LBP (p<0,05, Teste Tukey). O CLN mostrou aumento para OC em comparação aos demais grupos em ambos os períodos analisados (p<0,05, Teste Tukey). Conclusões: O CLN apresentou o melhor comportamento osteocondutor em defeitos críticos na calvária de coelhos.
Comparative evaluation of bone repairment with four different bone substitutes in critical size defects in rabbit's calvaria
Keywords: Bone; Biocompatible materials; Bone substitutes; Osso e ossos; Materiais biocompatíveis; Substitutos ósseos